Factors increasing the risk for food addiction in Ecuadorian students - Reivan Ortiz, Geovanny Genaro; Campoverde, Ximena; Vinañzaca, Juan; Estrada, Johanna; Yanza, Rafael; Granero, Roser (Frontiers in Psychiatry, 2024)
Background: Food addiction (FA) is a construct that has gained interest in recent years, but its relevance in the Ecuadorian population has not yet been explored. The aims of this work were to explore the differences in the psychological profile (including FA) between university students from Ecuador, and to identify the underlying the structure of the relationships of the FA severity level through a mediational model.The sample consisted of 972 university students, females and males (mean age 20.1 yearsold, SD=2.6), recruited from four Ecuadorian regions. The assessment tools included an unidimensional scale of FA, eating related measures, emotion regulation state, impulsivity, and psychopathology state. Path analysis modeled the direct and indirect effects explaining the FA severity level.The results indicated that higher psychopathological levels were associated with FA.Likewise, no differences in FA were observed between the Ecuadorian regions. The path analysis suggested that older age, female gender and higher difficulties in emotional regulation, impulsivity, negative mood and anxiety, trigger disordered eating; next, more impaired eating behavior impacted on the FA level.FA is a complex clinical entity that includes multiple components related with eating disorder and other mental health problems. The results of this work provide empirical knowledge for designing evidence-based prevention and treatment strategies.